Audit Committee, Board of Directors, and Sustainability Reporting: the Moderating Role of Gender Diversity - Silvi Khoerunnisa Nurandini; Frido Saritua Simatupang (Summa : Journal of Accounting and Tax, 2026)
This research seeks to analyse the relationship between audit committees and boards of directors and sustainability report disclosure in financial sector businesses listed on the Singapore Exchange from 2022 to 2024. It will take gender diversity into consideration as a moderating variable. Companies' sustainability reports are rising in importance as a measure of their performance in response to rising stakeholder demands for more openness and responsibility across economic, social, and environmental domains. Using an associative method, this study applied a quantitative approach. Financial reports, sustainability reports, and annual reports were the sources of secondary data. Using a purposive selection technique, eighteen businesses from the financial industry made up the study sample. We used EViews 13 to do our data analysis, which included panel data regression and Moderated Regression Analysis (MRA). The findings indicate that, to some extent, the disclosure of Sustainability Reports is unaffected by the audit committee and board of directors. Sustainability Report disclosure is, however, concurrently influenced by the board of directors and the audit committee. Furthermore, the publication of Sustainability Reports did not improve the interaction between the audit committee and the board of directors, even after accounting for gender diversity. Based on these results, it seems that integrated corporate governance structures are the best way to promote sustainability disclosure.